Slovenska nacionalna knjižnica - Kodrič-Dačić, Eva (Knjižnica, 2005)
The article introduces the national library as the central national cultural institution and presents its place in the awareness of the Slovenes. It also identifies the reasons for the attitude of the Slovene lay and professional communities towards this institution. The national library is defined as a generic term and linear quantitative comparisons between the national libraries of the world are being questioned. The historical development of the Slovene national library is briefly described from its original conception of carrying out the national functions in the 19th century until its first official recognition after World War II. The current functions of the national library are presented and there is also a description of the way it has undertaken to develop the Slovene library system.
Keywords: nacionalne knjižnice; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana; zgodovinski pregledi